2010
DOI: 10.3402/meo.v15i0.5295
|View full text |Cite
|
Sign up to set email alerts
|

Ready or not? Expectations of faculty and medical students for clinical skills preparation for clerkships

Abstract: BackgroundPreclerkship clinical-skills training has received increasing attention as a foundational preparation for clerkships. Expectations among medical students and faculty regarding the clinical skills and level of skill mastery needed for starting clerkships are unknown. Medical students, faculty teaching in the preclinical setting, and clinical clerkship faculty may have differing expectations of students entering clerkships. If students’ expectations differ from faculty expectations, students may experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 24 publications
1
58
0
1
Order By: Relevance
“…A recent study reported that students had higher expectations of their own skill development than clinical faculty had. 24 This finding may be related to students' desire to impress faculty so that they "earn" learning opportunities.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study reported that students had higher expectations of their own skill development than clinical faculty had. 24 This finding may be related to students' desire to impress faculty so that they "earn" learning opportunities.…”
Section: Discussionmentioning
confidence: 94%
“…8,9 In our experience, written test performance is statistically associated with non-compliance scores, suggesting that proper timely intervention by the class director to decrease non-compliance score may modify student competence. Long-term student outcomes need to be evaluated to determine if our observations and class will be effective in improving premedical education.…”
Section: Discussionmentioning
confidence: 77%
“…The high level of agreement on maneuvers between PDCDs and IMCDs may bridge the gap between preclinical faculty, clerkship faculty, and students' differing expectations of what skills are needed on entry to clerkships. 9 The third issue raised by our survey respondents was how to address the need for students to practice and achieve proficiency in certain technically challenging maneuvers that may require regular practice, even though they might not be clinically necessary. Their concern is supported by Wu et al, 23 who showed that clerkship students have relatively low self-confidence in certain skills such as the fundoscopic exam, measuring jugular venous pulse, and detecting thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that students find performing a comprehensive set of physical exam maneuvers overwhelming and may have higher performance expectations of themselves than their educators do of them. 9 Other research demonstrates that students have difficulty effectively applying what they learn in the preclerkship curriculum to clinical cases. 10 It is also possible that if students are asked to routinely perform many maneuvers without clinical or educational rationale, they may begin to feel that the physical examination as a whole lacks utility.…”
mentioning
confidence: 98%